Walras–Bowley Lecture: Market Power and Wage Inequality - Deb, Shubhdeep; Eeckhout, Jan; Patel, Aseem; Warren, Lawrence (Econometrica, 2024)
We propose a theory of how market power affects wage inequality. We ask how goods and labor market power jointly determine the level of wages, the skill premium, and wage inequality. We then use detailed microdata from the U.S. Census Bureau between 1997 and 2016 to estimate the parameters of labor supply, technology, and the market structure. We find that a less competitive market structure lowers the average wage of high‐skilled workers by 11.3%, and of low‐skilled workers by 12.2%, contributes 8.1% to the rise in the skill premium, and accounts for 54.8% of the increase in between‐establishment wage variance.